2007
DOI: 10.4097/kjae.2007.53.3.s14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 6% Hydroxyethyl Starch 130/0.4 on Hemostasis and Hemodynamic Efficacy in Off-pump Coronary Artery Bypass Surgery: a Comparison with 6% Hydroxyethyl Starch 200/0.5

Abstract: Background:This study was designed to compare the effect of low-molecular 6% hydroxyethyl starch (HES) 130/0.4 on hemostasis and hemodynamic efficacy with that of medium-molecular 6% HES 200/0.5 in patients undergoing off-pump coronary artery bypass surgery.Methods: Forty-eight patients were randomized to receive up to 33 ml/kg of either 6% HES 130/0.4 or 6% HES 200/0.5. Hemodynamic variables and blood tests including thromboelastography were measured 10 min after induction (baseline value, T0), 5 min after ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…[4] Though colloids such as hydroxyl ethyl starch (HES) are effectively used for intraoperative volume replacement and plasma volume expansion, they may cause coagulopathy and result in postoperative blood loss. [5,6] The search for the newer modes to facilitate reduction in perioperative blood loss continues, the use of fibrinolytic inhibitors such as TA may be an effective method to promote blood conservation; but, the possible complications of thrombosis of coronary artery graft, precludes their regular use in coronary artery bypass graft surgeries. [1,6,7] In this study we assessed the hemostatic effects of concomitant use of HES and TA.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Though colloids such as hydroxyl ethyl starch (HES) are effectively used for intraoperative volume replacement and plasma volume expansion, they may cause coagulopathy and result in postoperative blood loss. [5,6] The search for the newer modes to facilitate reduction in perioperative blood loss continues, the use of fibrinolytic inhibitors such as TA may be an effective method to promote blood conservation; but, the possible complications of thrombosis of coronary artery graft, precludes their regular use in coronary artery bypass graft surgeries. [1,6,7] In this study we assessed the hemostatic effects of concomitant use of HES and TA.…”
Section: Introductionmentioning
confidence: 99%
“…These results may be induced not only from hemodilution but also due to their pharmacological properties (Jin and Yu, 2010). Biochemical data representing liver and kidney function remained within normal limit after the off-pump coronary artery bypass surgery when using HES (Kim et al 2007). However, in meta-analysis conducted in 2012 concluded that the poor quality and small size of available studies don't allow the benefits and risks of HES 130/ 0.4 to be reliably estimated (Gattas et al, 2012).…”
Section: Introductionmentioning
confidence: 89%